2011
DOI: 10.1097/mpg.0b013e318202a3e5
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux in Young Children Treated for Esophageal Atresia: Evaluation With pH‐Multichannel Intraluminal Impedance

Abstract: Our data show that in young patients the majority of refluxes are not acid. This implies that the incidence of GER may be underestimated if pH-metry is used. The pH-MII is an ideal test in children because it studies both GER with its characteristics and motility pattern. The quality of reflux does not seem to influence the onset of symptoms that are related to an impaired esophageal clearance. Hence, this technique could be useful to study patients treated for EA, avoiding the onset of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 27 publications
3
44
2
3
Order By: Relevance
“…Di Pace et al [21], using MII/pH, demonstrated that in children who underwent a corrective operation for EA/TEF, gastroesophageal reflux disease was frequent and that the time of bolus clearance, acid clearance and time of bolus passage were pathological. Catalano et al [22] demonstrated a correlation of gastroesophageal reflux disease with non-acid reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Di Pace et al [21], using MII/pH, demonstrated that in children who underwent a corrective operation for EA/TEF, gastroesophageal reflux disease was frequent and that the time of bolus clearance, acid clearance and time of bolus passage were pathological. Catalano et al [22] demonstrated a correlation of gastroesophageal reflux disease with non-acid reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Of these high refluxes, 47% were weakly acidic and 53% were acidic. In another study, 62% of coughs were associated with reflux in children ≤1 year old, and 58% of coughs were associated with reflux in children >1 year old (39). Cough episodes were more commonly seen with acid reflux, though compared to children >1 year old, younger children had more frequent cough episodes related to non-acid reflux.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Comparing infants with EA and controls with GER, the mean ACT and mean BCT are significantly longer in the EA group (39). Correlation between symptoms and clearance time in the EA group showed that the median ACT and BCT were significantly shorter in patients without symptoms than in those with symptoms.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of sensitivity of the used technologies and/or the absence of an integrated analysis method of manometry and impedance recordings or the fact that normal clearance can also be achieved with abnormal motility patterns may be potential reasons (8). Given children with EA may undergo many radiological investigations over their lifetime, a non-radiological alternative for radiology requires investigation (911). …”
Section: Current Diagnostic Methods To Investigate Dysphagia In Eamentioning
confidence: 99%